Binge eating in bariatric surgery candidates: The role of insecure attachment and emotion regulation. (1st August 2015) - Shakory, Sharry; Van Exan, Jessica; Mills, Jennifer S.; Sockalingam, Sanjeev; Keating, Leah; Taube-Schiff, Marlene
Highlights: We investigated the relationship between insecure attachment and binge eating. Difficulties in emotion regulation were found to mediate this relationship. Higher anxious attachment was associated with greater binge eating severity. Higher avoidance attachment was associated with lower binge eating severity. Targeting emotion regulation skills may reduce binge eating in bariatric candidates. Abstract: Binge eating has a high prevalence among bariatric patients and is associated with post-surgical weight gain. This study examined the potential mediating role of emotion regulation difficulties in the relation between attachment insecurity and binge eating among this population. Participants were 1388 adult pre-bariatric surgery candidates from an accredited bariatric surgery assessment centre in Toronto, Ontario. Participants completed measures of psychological functioning, including attachment style and emotion regulation. Mediation analyses revealed that difficulties with emotion regulation mediated a positive association between insecure-anxious attachment and binge eating. An insecure-avoidant attachment was found to have a non-significant association with binge eating when examining the total effect. However, when difficulties with emotion regulation were controlled for in the model to examine its role as a mediator, this association became significant, and emotion regulation difficulties also mediated the relationship between attachment avoidance and binge eating. These findings suggest that difficulties in emotion regulation may be an important clinical issue to address in order to reduce binge eating in adult bariatric surgery candidates.